Sward structure and patterns of defoliation of signal grass (Brachiaria decumbens) pastures under different cattle grazing intensities - Busqué, J.; Herrero, Mario (2001)
The effects of 3 different stocking rates (1, 2 and 3 cows/ha/yr) on sward structure and the amount and pattern of live leaf defoliation were studied at different hierarchical levels within swards of signal grass (Brachiaria decumbens ) pastures. Permanently marked plants and tillers were followed non-destructively during 8 consecutive grazing periods for each stocking rate treatment. Leaf and stem lengths were measured before and after the introduction of cattle for all marked tillers. The vertical distribution of leaves and stems within the sward was quantified and the fate of tillers after grazing was also considered. Vertical live leaf weight distributions in the canopy followed those of their apical meristem heights. The proportion of tillers defoliated per plant mainly explained the proportion of live leaf defoliated per plant at different stocking rates. The proportion of tillers decapitated during grazing was related to the proportion of tillers defoliated per plant. Apical meristem height was the main physical barrier to leaf defoliation upon a minimum leaf height of 2–4 cm, under which leaves were inaccessible to cattle. Different stocking rates created different tiller heights and canopy structures in the medium term, but did not affect the pattern of defoliation relative to the height of the apical meristem.